2021
DOI: 10.3390/antiox10101564
|View full text |Cite
|
Sign up to set email alerts
|

An Unrecognized Fundamental Relationship between Neurotransmitters: Glutamate Protects against Catecholamine Oxidation

Abstract: Neurotransmitter catecholamines (dopamine, epinephrine, and norepinephrine) are liable to undergo oxidation, which copper is deeply involved in. Catecholamine oxidation-derived neurotoxicity is recognized as a pivotal pathological mechanism in neurodegenerative diseases. Glutamate, as an excitatory neurotransmitter, is enriched in the brain at extremely high concentrations. However, the chemical biology relationship of these two classes of neurotransmitters remains largely unknown. In the present study, we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 82 publications
(102 reference statements)
1
10
0
1
Order By: Relevance
“…Thus, the previous proposal that l -theanine could be hydrolyzed into glutamate in the intestine and liver has no solid evidence. The observed role of l -theanine in pro-oxidant actions of EGCG implies that glutamate may participate in reducing pro-oxidant properties of EGCG because it has been found that glutamate can inhibit dopamine oxidation via chelating copper . However, glutamate is not a suitable supplemental agent for reducing the pro-oxidant role of EGCG because individuals who consume elevated amounts of monosodium glutamate in their diet are more likely to suffer from headaches and short-term elevated blood pressure. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the previous proposal that l -theanine could be hydrolyzed into glutamate in the intestine and liver has no solid evidence. The observed role of l -theanine in pro-oxidant actions of EGCG implies that glutamate may participate in reducing pro-oxidant properties of EGCG because it has been found that glutamate can inhibit dopamine oxidation via chelating copper . However, glutamate is not a suitable supplemental agent for reducing the pro-oxidant role of EGCG because individuals who consume elevated amounts of monosodium glutamate in their diet are more likely to suffer from headaches and short-term elevated blood pressure. , …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1a, 50 mM copper sulfate solution exhibited a light blue color, and the addition of L-theanine at a molar ratio of 1−10 (L-theanine/divalent copper) dose-dependently enhanced the blue color, demonstrating that L-theanine, like its structural analogue glutamic acid or glutamate, formed a complex with copper. 14,19 EGCG is liable to autoxidation in neutral to alkaline environments; 8,19 however, the autoxidation of EGCG alone is trivial at pH 6.0 as reflected by OD 410nm values (Figure 1b). Under this circumstance, divalent copper ions greatly enhanced EGCG oxidation (Figure 1b).…”
Section: L-theanine Forms a Complex With Copper Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang W. et al report interesting and original new observations regarding the crosstalk between the excitatory neurotransmitter glutamate and dopamine oxidation [3]. This study identifies several mechanisms by which glutamate might regulate dopamine oxidation, a process that is recognized to have a toxic impact in Parkinson's disease (PD).…”
mentioning
confidence: 94%